Expectations And Prospects For Professional And Personal Advancement Among Russian; The European Proceedings of Social & Behavioural Sciences (EpSBS); Vol. 38 : Lifelong Wellbeing in the World (WELLSO 2017) - Dreval A. N. Anatoly Nikolaevich; Ivanova V. S. Vera Stepanovna; Trubchenko T. G. Tatiana Grigorievna; Shaftelskaya N. V. (2018, 2018)
Title screen